The Analysis Four Curriculum Development Approach in English Teaching - Almadani, Tiara Nur Fatimah; Mirza, Akhmad Ali; Qamariah, Zaitun (Journal Of Foreign Language Learning and Teaching, 2023)
The curriculum is a collection of educational learning strategies that are conceived, produced, and implemented to accomplish a certain objective. The process of developing a curriculum is broken down into phases, but it can also be thought of as a set of actions that go into developing a new curriculum or improving an old one. Approaches curriculum development include two models, Top-Down approach (administrative model) and Grass-Root approach. The Tyler curriculum development model, Taba's curriculum development model, Olivia's curriculum development model, and Beauchamp's curriculum development model are the four curriculum development models now used in education. When introducing English instruction in Indonesia, this curricular model is utilized as a guide. This article will make an effort to provide a theoretical overview of several curriculum-building methodologies and approaches. The development of the school curriculum may be reviewed in this essay, with a focus on English language instruction. How effective and efficient is the Indonesian model of the curriculum for teaching English? It's crucial for aspiring teachers to comprehend how the school curriculum is created.